2005
DOI: 10.1270/jsbbs.55.213
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Recombinant Human Lactoferrin in Transgenic Javanica Rice

Abstract: The objective of the present study was to develop a functional crop that could contribute to the maintenance and improvement of human health by the introduction of the human lactoferrin (hLF) gene. Lactoferrin is an 80-kDa iron-binding glycoprotein that has been considered to play many biological roles, including the regulation of iron absorption, protection against microbial and virus infection, stimulation of the immune system and cellular growth promotion. We introduced two different constructs containing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…The demand for LF has stimulated the development of various recombinant technologies for an efficient and economical production of LF. One successful product is the recombinant rice lactoferrin (rLF; Nandi et al 2005;Rachmawati et al 2005). The rLF has the same amino acid sequence and three-dimensional structure as hLF.…”
Section: Lactoferrinmentioning
confidence: 99%
“…The demand for LF has stimulated the development of various recombinant technologies for an efficient and economical production of LF. One successful product is the recombinant rice lactoferrin (rLF; Nandi et al 2005;Rachmawati et al 2005). The rLF has the same amino acid sequence and three-dimensional structure as hLF.…”
Section: Lactoferrinmentioning
confidence: 99%
“…To meet these aspects, large amounts of hLF are required. Although hLF has been expressed in various systems [1,10,12,13,16,19,26,28], the potential nutritional and therapeutic application of hLF has not been exploited so far due to the lack of an inexpensive method for the production of sufficient quantities of functional LF for commercial use. Ying et al [28] have reported the production of rhLF in the methylotrophic yeast Pichia pastoris, but the level was moderate, with the highest production of 115 mg·L −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic rice cv. Rojolele expressing recombinant human lactoferrin gene was obtained through Agrobacterium-mediated transformation (Rachmawati et al, 2005). Transgenic lines TR-7, TR-8, and TR-10 carried mature human lactoferrin gene was fused to the DNA sequence encoding the rice glutelin signal peptide with the constitutive maize ubiquitin-1 promoter.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Rojolele has become a popular local rice variety in Central Java and is distributed throughout Indonesia because it has an aromatic fragrance and a delicious taste (Mudjisihono et al, 2002). Rachmawati et al (2005) have been introduced the lactoferrin gene into Javanica rice cv. Rojolele.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation